PENGARUH SUSU KACANG KUDA DAN JAHE UNTUK ANEMIA PADA IBU HAMIL - Fitria Meiriza SyahastI, Zurni Seprina, (Menara Ilmu, 2018)
Anemia in pregnant mother is helath problem which have related with high incidents andcomplications, can attack for mother or fetus. Many action have been done for preventincident anemia in pregnant mother like improvement of nutritional intake, program ofgiving ASI, and giving zat Besi long time before pregnant. But that effort not statisfying soneed alternative materials for nutrition in pregnant mother and Very much zat besi relatedwith Hemoglobin levels. In reality many pregnant mother not like drink cows milk sohorse milk bean with ginger expected can meet the nutritional need for pregnant mother atonce can repaired anemia problem in pregnant mother. The Purpose this reaserch forknow effect anti anemia horse milk bean with ginger in pregnant mother and from horsemilk bean with ginger will created product health drink for lower anemia incident. Thisresearch have metode kuantitatif analitic experiment by means of cross sectional. Thisresearch pleace in Batu Besurat with responden 49 pregnant mother. The result ofresearch with Uji T showing Hemoglobin levels be high on meaningfull with P Value(p<0,05) in second month compared with first month. This means horse milk bean withginger effective for lower anemiaKeymord: anemia, horse, ginger